The Establishment of Ramadan Principality - Fatma Akkuş Yiğit (Gazi Akademik Bakış)
Ramadan Principality is a Turkish state which was established in Cukurova, having Adana as center, in 14th century. Uc Ok Turcoman, constituting this state, were Turkish raider lords who served Mamluks from the beginning of the establishment. They showed maximum effort during the campaigns by Mamluks onto the Armenians living in Cukurova, and after the collapse of this state, they secure their position in that region as being subject to Mamluks. Insomuch that Ramazan Beg, signified as “Turcoman Emir”, was accommodated by Mamluks Sultan in Cario, and dressed Khalat. Mamluks attached great importance to the region forming the north border in which Ramadanids was established. They formed three regentships named as Ayas, Tarsus and Sis and constantly supervised these three cities by sending regents from the capital city, Cairo. Despite the attitude of Mamluks, Ibrahim Beg, successor of Ramadan, who took courage from the achievements of Dulkadirids, allying with them revolted against Mamluks, but this revolt did not produce result and moreover cost his life. Since the histories of Ramadan and Dulkadir Principalities, established as subjected to Mamluks in close regions, crossed with each other’s frequently, activities of Dulkadirids will also be mentioned where relevant. But what we know about Turcoman is limited to the information given by Mamluks’ chronicles.